2022
DOI: 10.2147/dmso.s380053
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin Alleviates Hepatic Steatosis in NAFLD via the mTOR Dependent Pathway

Abstract: Purpose In this study, we aimed to investigate the effect of follistatin (FST) on hepatic steatosis in NAFLD and the underlying mechanism, which has rarely been reported before. Methods Liver samples from NAFLD patients and normal liver samples (from liver donors) were collected to investigate hepatic FST expression in humans. Additionally, human liver cells (LO2) were treated with free fatty acid (FFA) to induce lipid accumulation. Furthermore, lentivirus with FST over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Finally, in this review we focused on the cytokines secreted by the muscle and having an effect on the liver, however, physical exercise also has an impact on the over-expression of liver-secreted cytokines, the hepatokines, which in turn, can have beneficial autocrine effects on the liver. For example, hepatic follistatin, whose expression is increased in NAFLD patients, inhibits lipid accumulation and lipogenesis through the mTOR pathway [ 79 ]. Thus, according to the effects of physical exercise on the expression of liver cytokines and of other organ-derived cytokines, it could be of interest to also study their effects on NAFLD’s different stages, to explore the range of possible NAFLD therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in this review we focused on the cytokines secreted by the muscle and having an effect on the liver, however, physical exercise also has an impact on the over-expression of liver-secreted cytokines, the hepatokines, which in turn, can have beneficial autocrine effects on the liver. For example, hepatic follistatin, whose expression is increased in NAFLD patients, inhibits lipid accumulation and lipogenesis through the mTOR pathway [ 79 ]. Thus, according to the effects of physical exercise on the expression of liver cytokines and of other organ-derived cytokines, it could be of interest to also study their effects on NAFLD’s different stages, to explore the range of possible NAFLD therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Yano et al demonstrated that fibroblast growth factor 21 (FGF21), an endocrine growth factor, induced the phosphorylation of AMPK at Thr172 and Raptor at ser792 and suppressed mTOR at ser2448, which downregulated mTORC1 signaling and contributed to improved liver steatosis in HFD-fed mice [ 136 ]. In addition, overexpression of follistatin, (FST), a gonadal protein that specifically inhibits follicle-stimulating hormone release, alleviated lipid accumulation and lipogenesis, whereas FST knockdown aggravated hepatic steatosis via suppressing the mTOR pathway, therefore, may have a potential to become a therapeutic target in NAFLD/NASH [ 137 ]. Very recently Chen et al have shown that Ufm1-specific ligase 1 (Ufl1) and Ufm1-binding protein 1 (Ufbp1), which are putative targets of ubiquitin-fold modifier 1 (Ufm1), prevent liver fibrosis, subsequent steatohepatitis, and HCC development in diethylnitrosamine DEN-treated mice by inhibiting the mTOR pathway [ 138 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%